Morphometric Characteristics of Mangrove Snails (Telescopium telescopium) in the Mangunharjo Mangrove Forest, Semarang City - Muhammad Adi Rizaldi; Sri Redjeki; Retno Hartati (Masyarakat Moluska Indonesia, 2022)
ABSTRACT Mangroves can play a role as in mollusk life cycles because the mangrove environment provides food. The gastropod species Telescopium telescopium is found in the mangrove forest of ​​Mangunharjo, Semarang City, Indonesia. Mangunharjo Village is an area that has experienced environmental degradation due to changes in land use. The reduction in ​​​​mangrove forests area will have an impact on T. telescopium survival and condition including shell shape and length. This study calculated the morphometric differences between T. telescopium populations based on environmental factors in the Mangunharjo mangrove forest. The study used a descriptive exploratory method with purposive sampling from November to December 2021. Water quality data collected simultaneously with T. telescopium sampling included temperature, salinity, pH and sediment substrate type. The results showed that the population abundance values ​​were 0.44 ind/ha (Station I), 0.18 ind/ha (Station II) and 0.21 ind/ha (Station III). Length weight relationship showed negative allometric (b < 3). T. telescopium sex ratio 1: 0.80. The T. telescopium shells were characterized by a round conical shape with a pointed and a brownish-black outer shell surface with a spiral lines and morphometric measurements (length, diameter, weight) rang from 3.58-9.51 cm, 1.51-4.43 cm and 3-69 g at Station I; 5.06-9.80 cm, 2.34-5.01 cm and 7-87 g at Station II; 3.7-9.97 cm, 1.93-5.01 cm and 5-87 g at Station III. The morphometric measurements of T. telescopium length ranges from 3.58-9.97 cm, diameter 1.51-5.01 cm and total weight 3-87 g, which is dominated by individuals with length classification in large category and class classification of diameter and total weight are included in the medium category.